In vitro studies of magnetically enhanced transfection in COS-7 cells - Ang, Derrick (2011)
In the magnetically enhanced gene delivery technique, DNA complexed with polymer coated aggregated magnetic nanoparticles (AMNPs) is used for effecting transfection. The aim of this study is to examine the relationship between transfection efficiency and the physical characteristics of the polymer coated AMNPs. In vitro studies of transfection efficiency in COS-7 cells were carried out using pEGFP-N1 and pMIR-REPORT complexed polyethylenimine (PEI) coated iron oxide magnetic nanoparticles. PEI coated AMNPs (PEI-AMNPs) with average individual particle diameters in the range of 8 nm to 30 nm were studied and characterized by transmission electron microscopy, vibrating sample magnetometry, X-ray diffractometry, thermal gravimetric